Evolution engine technology in exhaust gas recirculation for heavy-duty diesel engine - Mohd Rodzi, Siti Nur Aizierah; Zanalli, Sophia; Khalid, Amir; Manshoor, Bukhari; Ngadiron, Zuraidah (Penerbit UTHM, 2020)
In this present year, engineers have been researching and inventing to get the optimum of less emission in every vehicle for a better environmental friendly. Diesel engines are known reusing of the exhaust gas in order to reduce the exhaust emissions such as NOx that contribute high factors in the pollution. In this paper, we have conducted a study that EGR instalment in the vehicle can be good as it helps to prevent highly amount of toxic gas formation, which NOx level can be lowered. But applying the EGR it can lead to more cooling and more space which will affect in terms of the costing. Throughout the research, fuelling in the engine affects the EGR producing less emission. Other than that, it contributes to the less of performance efficiency when vehicle load is less.